Management Peculiarities of Patients with Intramural Hematoma of the Ascending Aorta: a Clinical Case - Varbanets, S. V.; Telehuzova, O. V.; Chernetskyi, Ye. O.; Tsvyk, A. S. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Intramural hematoma of the ascending aorta has been considered a rare form of an acute aortic syndrome, remaining a tremendous clinical problem in management paradigm. Purpose. To present the clinical case of a patient with intramural hematoma of the ascending aorta (type A) and to analyze the surgical management. Materials and methods. A 52-year-old female patient was hospitalized with complaints for chest pain over the last year which abruptly increased a few days before hospitalization during high-intensity exercise. A full range of additional examinations was provided. Results and discussion. Hematoma occurs without the formation of a false lumen and in the absence of the initial limit of the vascular wall rupture. Intramural hematoma of the ascending aorta requires careful analysis and management through the combination of well-established recommendations and a personalized approach. Prosthetic repair of the ascending aorta was performed with the formation of hemiarch distal anastomosis using retrograde cerebral perfusion. Conclusion. Choosing the optimal management is an important clinical task with implications affecting primary and long-term outcomes. Based on numerous guidelines and recommendations, we have developed an integrated rapid algorithm to pick-up the most suitable management option for the patient with intramural hematoma of the ascending aorta.